2017
DOI: 10.1016/j.omto.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical Assessment of C134, a Chimeric Oncolytic Herpes Simplex Virus, in Mice and Non-human Primates

Abstract: Oncolytic herpes simplex virus (oHSV) type I constructs are investigational anti-neoplastic agents for a variety of malignancies, including malignant glioma. Clinical trials to date have supported the safety of these agents even when directly administered in the CNS. Traditional pre-clinical US Food and Drug Administration (FDA) toxicity studies for these agents have included the use of two species, generally including murine and primate studies. Recently, the FDA has decreased its requirement of non-human pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Unlike many lethal cancers, glioblastomas rarely metastasize out of the central nervous system (CNS), and a majority of patients suffer recurrence within 2–3 cm of the original resection cavity ( Wallner et al, 1989 ); this behavior has prompted investigation of local therapies, including oncolytic viruses ( Martuza et al, 1991 ; Alonso et al, 2012 ; Kaufmann and Chiocca, 2014 ; Miska et al, 2016 ; Cassady et al, 2017 ; Cattaneo and Russell, 2017 ). Efficacy of virotherapy against tumors depends on the ability to infect and kill tumor cells specifically ( Cattaneo and Russell, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike many lethal cancers, glioblastomas rarely metastasize out of the central nervous system (CNS), and a majority of patients suffer recurrence within 2–3 cm of the original resection cavity ( Wallner et al, 1989 ); this behavior has prompted investigation of local therapies, including oncolytic viruses ( Martuza et al, 1991 ; Alonso et al, 2012 ; Kaufmann and Chiocca, 2014 ; Miska et al, 2016 ; Cassady et al, 2017 ; Cattaneo and Russell, 2017 ). Efficacy of virotherapy against tumors depends on the ability to infect and kill tumor cells specifically ( Cattaneo and Russell, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…T-Vec, approved for use in advanced melanoma, is similar to G47Δ, except that it has an intact ICP6 and expresses granulocyte-macrophage colony-stimulating factor (GM-CSF) (65), but may retain some neurovirulence (66). Expressing PKR inhibitors (human cytomegalovirus [HCMV] IRS1 in C134 and HSV-1 Us11 in C122) from the CMV IE promoter can overcome the growth defects of ␥34.5 Ϫ HSV-1; however, C122 (ICP47 ϩ ICP6 ϩ ) exhibited some neurovirulence in mice (62). The extreme negative effect of ␥34.5 loss on virus replication became fully apparent only when GSCs were isolated and tested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that early generation viruses that were conservatively designed for safety were often unable to replicate effectively in these tumor cells, and this likely hampered their ability to elicit a sustained antitumor immune response 104, 114. To overcome this shortcoming, we and others have engineered next-generation viruses with improved replication in tumor cells or viruses that activate immunostimulatory pathways or carry transgenes that stimulate different arms of the antitumor immune response 106, 115, 116, 117. Based on early clinical successes, current strategies to target more resistant tumor types involve combining virotherapy with immunomodulatory agents, such as immune checkpoint inhibitors or agents that alleviate tumor-associated immunosuppression to extend viro-immunotherapeutic activity 60, 90, 118, 119, 120.…”
Section: Main Textmentioning
confidence: 99%